A alquimia do oráculo: buscar a transformação, tendo como estímulo o sistema simbólico - Oliveira, Jeronimo Moreira de (2007)
This thesis is useful to religion, religiousity and archetypes. The question is:- does understanding of the real and the imaginary conducts a person to a better situation in his/her life? To answer this question one would have to know the meaning of the phrase - a better situation in his/her live . Once the religiosity according to tell of the Other, these are, considered of moral tenor and the actions are used in the conduct as a sociologic vision to determine how these actions are done to the religious comprehension. How would be the mind s alchemy in old times seem through today s symbolic systems? Exemplifying, today, we have a CAVI (Ciclo de Aprendizagem Vivencial do Imaginário Imaginary s Lively Learning) very strong/virtual the technology that became CAV (Ciclo de Aprendizagem Vivencial Lively Learning Cycle) and the ours forefathers CAVI. The interaction of archetypes in the gender (father/mother) makes us comprehend the oracle s alchemy : seek the transformation as a stimulus the symbolic system of the CAV and CAVI together form the resultant.